2017
DOI: 10.1177/0040517517697642
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the transfer abilities of single layers on the heat and mass transport through multilayered outerwear clothing for cold protection

Abstract: This paper deals with performance properties related to human thermo-physiological comfort of three-layer textile systems used for the production of outerwear for cold protection. The transfer of heat and fluids through the compound single layers (woven and non-woven) is investigated and compared to the heat and mass transfer of the systems for clothing. Six characteristics are measured for both single layers and systems of layers: thermal resistance, air permeability, water vapor resistance, relative water va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Research in the field of heat transmission through individual textile layers-as opposed to clothing systems protecting against cold, in which the insulating layer is a nonwoven fabric-has shown that thermal insulation of the whole system is lower than the sum of the values for the individual layers. 11 Heat transportation through the system depends of the values of the layers' thermal insulation.…”
mentioning
confidence: 99%
“…Research in the field of heat transmission through individual textile layers-as opposed to clothing systems protecting against cold, in which the insulating layer is a nonwoven fabric-has shown that thermal insulation of the whole system is lower than the sum of the values for the individual layers. 11 Heat transportation through the system depends of the values of the layers' thermal insulation.…”
mentioning
confidence: 99%
“…Figures [12][13][14] give the linear regression equation and coefficients of determination describing the proportion of variance in the heat resistance that is predic from the pressure in the chamber. As can be seen from the figures, high values of the coefficient were characteristic for PICs C-0, C-1V, and C-2V at all three ambient temperatures (20 • C, 15 • C, and 10 • C).…”
Section: Measured Thermal Properties Of Picsmentioning
confidence: 99%
“…At the same time, this batting caused an undesirable accumulation of moisture in the jacket, which led to a longer drying rate. Another group of scientists focused on the investigation of the transfer abilities (both heat and mass transport) of single layers through a multilayered system [ 13 ]. They measured six characteristics important for the classification of transfer properties.…”
Section: Introductionmentioning
confidence: 99%
“…State-of-the-art textiles for daily use are usually sufficiently good at water vapor transmission to ensure comfort at the mild state (See Supplementary Note 1 and Supplementary Figs. 1-2 for more discussion) 24 . Nevertheless, the cooling performance of conventional textiles is to be improved when human body is in more intense scenarios, such as moderate/profuse perspiration situations in which liquid sweat is inevitably present.…”
mentioning
confidence: 99%